Spatial and Building Style Transformation of Madura Pendalungan Settlement in The Peri-Urban Area of Malang City : (Case Study: Baran Buring Village, Malang, East Java, Indonesia) - Titisari, Ema Yunita; Wulandari, Lisa Dwi; Yusran, Yusfan Adeputera (RUAS, 2025)
The Madura Pendalungan settlement on the peri-urban of Malang City has changed the style of building and spatial planning, along with the development of culture and the city. The focus of this research is on changes in the spatial layout and architectural style of Madura Pendalungan in Buring Baran Village, Malang City. This study uses a descriptive method. Data on spatial order and vernacular architectural styles were collected through field observations. The analysis was carried out by identifying changes in building style and spatial layout, both at the scale of buildings (houses) and residential clusters. The results of the study showed that houses experienced a change in building style along with a change in spatial layout. Modifications are also seen in the use of building materials and construction systems. Although the building plan shows a change in spatial layout, the basic structure of the space such as front-center-back, the pattern of rowing or grouping based on lineage, and the functional aspects of the space, tend not to change. This change is triggered by the trend of building styles followed by the community, changes in livelihoods and space needs, and land availability.